2012
DOI: 10.1021/cb300172e
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Highly Selective c-Src Kinase Inhibitor

Abstract: Generating highly selective probes to interrogate protein kinase function in biological studies remains a challenge and new strategies are required. Herein, we describe the development of the first highly selective and cell permeable inhibitor of c-Src, a key signaling kinase in cancer. Our strategy involves extension of traditional inhibitor design by appending functionality proposed to interact with the phosphate-binding loop of c-Src. Using our selective inhibitor, we demonstrate that selective inhibition i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
140
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 112 publications
(150 citation statements)
references
References 35 publications
10
140
0
Order By: Relevance
“…None of the effects was observed with PP3, a negative control for PP2. Recent studies reported that PP2 may inhibit other kinases with similar affinities and that it is less Src selective than the Src family kinase inhibitor dasatinib (Das) (4). Therefore, we also tested Das and found that it efficiently reduced FAK-p-Tyr…”
Section: Nrg1␤-induced Mtorc2-mediated Akt Phosphorylation At Sermentioning
confidence: 92%
“…None of the effects was observed with PP3, a negative control for PP2. Recent studies reported that PP2 may inhibit other kinases with similar affinities and that it is less Src selective than the Src family kinase inhibitor dasatinib (Das) (4). Therefore, we also tested Das and found that it efficiently reduced FAK-p-Tyr…”
Section: Nrg1␤-induced Mtorc2-mediated Akt Phosphorylation At Sermentioning
confidence: 92%
“…A diverse set of 1,5-triazole products can be found in these reports which cover a wide range of targets and target classes including various enzyme inhibitors, [203][204][205][206][207][208][209][210][211][212][213] kinases, [214][215][216][217] proteases, 110,112 antivirals 218 (see also chapter 5.3) G-protein coupled receptors (GPCRs), 219 ion channels, [220][221][222] heat shock proteins, 95 and tRNA ligands. 223 1,5-Triazole derivatives have shown activity against numerous cancer cell lines, 205,215,[224][225][226][227] and against the parasites Trypanosoma cruzi 70,228 and Plasmodium falciparum.…”
Section: Target-oriented Medicinal Chemistrymentioning
confidence: 99%
“…Several changed upon PP2, but not bosutinib or imatinib treatment, and, based on previous studies, these changes would not be expected to facilitate healing (Brandonisio et al, 2002;LimaJunior et al, 2013;Muller et al, 2003;Oghumu et al, 2010;Ritter and Korner, 2002;Santiago et al, 2004). Of note, PP2 inhibits multiple targets, not just SFKs (>50 targets were seen in Brandvold et al, 2012), and these off-target effects could contribute to its chemokine and cytokine profile. More studies of chemokine secretion after host manipulations like kinase inhibition might be beneficial for unraveling the pathogenesis of leishmaniasis.…”
Section: **P=00023 (Two-tailed T-test) (E)mentioning
confidence: 99%